The Impact of Server-Side Rendering on UI Performance and SEO - Karthik Vallamsetla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the impact of Server-Side Rendering (SSR) on UI performance and Search Engine Optimization (SEO) in modern web development. It examines how SSR addresses the challenges faced by Single-Page Applications (SPAs) and content-rich websites by improving initial page load times, enhancing crawlability, and facilitating faster indexing. The article delves into the technical aspects of SSR implementation, discussing popular frameworks like Next.js, Nuxt.js, and Angular Universal. It also analyzes the performance benefits of SSR, including reduced Time to First Contentful Paint (FCP) and improved SEO scores across various web application types and network conditions. The article further explores optimization techniques such as code splitting, caching strategies, and streaming SSR, providing a comprehensive overview of SSR's role in creating faster, more discoverable, and user-friendly web applications.
Keywords: Server-Side Rendering; Web Performance; Search Engine Optimization; Single-Page Applications; JavaScript Frameworks